Status of glycemic index of paddy rice grain (Oryza sativa L.) on infestation by storage pest Sitotroga cerealella. (December 2020) - Kumar, Awadhesh; Basana Gowda, G.; Sah, Rameswar Prasad; Sahu, Chandrasekhar; Biswal, Monalisa; Nayak, Sarangdhar; Kumar, Sudhir; Swain, Padmini; Sharma, Srigopal
Abstract: The harvested paddy rice grains are normally stored by growers under normal conditions. Paddy rice grains are natural food for storage pests like Sitotroga. cerealella, a major insect that appears during paddy storage. The changes in grain composition due to such insect infestation in relation to human health especially the alteration in their Glycemic Index (GI) value have not been studied so far. The present investigation was aimed at studying the effect of S. cerealella infestation on rice grain quality and glycemic index of stored paddy grains . Five diverse rice genotypes with different quality traits were evaluated for grain quality after S. cerealella infestation . The tolerance to insect and variation of grain quality varied with rice genotype significantly. The glycemic index, glycemic load, total carbohydrate, amylose content and resistant starch were affected to a great extent. The consumption of affected grains may create health issue due to imbalance in nutrition and unhygienic condition. Improper storage of paddy after harvesting and processing results in infestation by pests at a large scale. Thus, the grain quality needs to be evaluated to judge the suitability of affected grain for consumption. Graphical abstract: Image 1 Highlights: Sitotroga cerealella is a most destructive storage pest of stored rice grain. Its infestation affects grain quality and glycemic index value of stored paddy. Imbalance nutritional and unhygienic grains consumption may cause health problems.